Does speed equal quality? Time pressure impairs minimally invasive surgical skills in a prospective crossover trial. (August 2022) - von Bechtolsheim, F.; Schmidt, S.; Abel, S.; Schneider, A.; Wekenborg, M.; Bodenstedt, S.; Speidel, S.; Weitz, J.; Oehme, F.; Distler, M.
Abstract: Background: Time pressure can cause stress, subsequently influencing surgeons during minimally invasive procedures. This trial aimed to investigate the effect of time pressure on surgical quality, as assessed by force application and errors during minimally invasive surgical tasks. Methods: Sixty-three participants (43 surgical novices trained to proficiency and 20 surgeons) performed four laparoscopic tasks (PEG transfer, precise Cutting, balloon resection, surgical knot) both with and without time pressure. The primary endpoint was the mean and maximal force exertion during each task. Secondary endpoints were the occurrence of predefined errors and the self-assessed stress level. Results: Time pressure led to a significant shortening of the task time in all four tasks. However, significantly more errors were noticed under time pressure in one task (suture precision P < 0.001). Moreover, time pressure led to a significant increase in mean force in all tasks (PEG: P < 0.001; precision cutting: P = 0.001; surgical knot: P < 0.001; balloon: P = 0.004). In three tasks the maximal force application (PEG: P < 0.001; precision cutting: P < 0.001; surgical knot: P = 0.006) increased significantly. Performing the tasks under time pressure significantly increased the stress level. Cohort analysis revealed that time pressure impaired the performance of both, surgical novices and surgeons but novices were more strongly affected compared to surgeons. Conclusion: Time pressure during minimally invasive surgery may improve procedural time but impair the quality of surgical performance in terms of the incidence of errors and force exertion. Experience may only partially compensate for the negative influence of time pressure. Highlights: Time pressure can impair surgical skills in minimally invasive surgical tasks. Time pressure increases force exertion and occurrence of errors. Surgical novices and surgeons are both affected by time pressure, but novices more. The stress level due to time pressure is higher in surgical novices.